(untitled) (Research, Society and Development, 2021)
Objective: This study describes and characterize the cases of Haff disease reported in Brazil during the COVID-19 pandemic period. Descriptive and cross-sectional study using public data from the National Center for Strategic Information and Response in Health Surveillance nacional. The Risk Communication number 17 of 09/15/2021 was accessed. The description of suspected cases was extended to all Brazilian states where notifications occurred, from January 1, 2020, to September 15, 2021. There was an increase in cases of Haff’s disease in Brazil, from 2020 onwards, with 46 in the Northeast region of Brazil. Eighty-five cases and three deaths were reported between January and September 2021 in the North, Northeast, South and Midwest regions. Most cases occurred in regions of greater heat such as the coastal region of the Northeast and around regions of the Amazon River Basin. A critical period for coping with the SARS-CoV-2 virus pandemic in Brazil, cases of disease of Haff could be reported in various regions of country. Despite the etiological suspicions, studies, and follow-up of the cases, it is still not possible to affirm that the disease is caused by biomolecules of the Palytoxin-Like Toxins group. The possible identification of the responsible toxin(s) will be essential for a complete understanding of the etiopathogenic mechanism of the disease and adequate development of prevention, treatment, and cure measures.